From the Feminist Upheaval to Public Art. The Far West of Opportunities - García-Oliveros, Elena (Re-visiones, 2024)
In the last decades, women's artistic practices have questioned the places to create, contemplate and show art. Women have thus contributed substantially to the evolution of the concept of "art" and its institutions. Why is the feminist movement essential in the definition of today's public art? What were women artists looking for, what were they escaping from when they experimented with these new trends? What relation does feminist cyberart have with the proposals initiated in the 1970s? Why do artists in the field redefine the concept of authorship? These are some of the questions that shaped the encounter between Toxic Lesbian and the American artist Suzanne Lacy on May 6, 2014, in conjunction with Intermediae Matadero, Madrid. Gloria G. Durán's and Lila Insúa's students, from the Faculty of Fine Arts, Universidad Complutense de Madrid, participated in this encounter.